Synergistic effects of Inward Rectifier (I(K1)) and Pacemaker (I(f)) Currents on the Induction of Bioengineered Cardiac Automaticity - Tse, Hung-Fat (2009)
INTRODUCTION: Normal heart rhythms originate in the sinoatrial node. HCN-encoded funny current (I(f)) and the Kir2-encoded inward rectifier (I(K1)) counteract each other by respectively oscillating and stabilizing the negative resting membrane potential, controlling action potential firing. Therefore, I(K1) suppression and I(f) overexpression have been independently exploited to convert cardiomyocytes (CMs) into AP-firing bioartificial pacemakers. Although the two strategies have been largely assumed synergistic, their complementarity has not been investigated. METHODS AND RESULTS: We explored the inter-relationships of automaticity, I(f) and I(K1) by transducing single left ventricular (LV) CMs isolated from guinea pig hearts with the recombinant adenoviruses Ad-CMV-GFP-IRES-HCN1-ΔΔΔ and/or Ad-CGI-Kir2.1 to mediate their current densities via whole-cell patch clamp technique at 37°C. Results showed that Ad-CGI-HCN1-ΔΔΔ- but not Ad-CGI-Kir2.1-transduction induced automaticity (181.1±13.1 bpm). Interestingly, Ad-CGI-HCN1-ΔΔΔ/Ad-CGI-Kir2.1 cotransduction significantly promoted the induced firing frequency (320.0±15.8 bpm; p<0.05). Correlation analysis revealed that the firing frequency, phase 4 slope and APD(90) of AP-firing LV CMs were correlated to I(f) (R(2)>0.7) only when -2>I(K1)>-4 pA/pF but not to I(K1) over the entire I(f) ranges examined (0.02<R(2)<0.4). Unlike I(f), I(K1) displayed correlation to neither the phase 4 slope (R(2)=0.02) nor phase 4 length (R(2)=0.04) when -2>I(f)>-4 pA/pF. As anticipated, however, APD(90) was correlated to I(K1) (R(2)=0.4). CONCLUSION: We conclude that an optimal level of I(K1) maintains a voltage range for I(f) to operate most effectively during a dynamic cardiac cycle.